The Influence of Competence and Training on Employee Performance through Motivation at the Environmental Service Office of Jambi Province - Suryanda, Hary; Bukit, Pantun; Akbar, Ali (Dinasti Publisher, 2025)
This study aims to analyze the influence of competence and training on employee performance through motivation as an intervening variable at the Environmental Service Office of Jambi Province. The research population consists of all 101 Civil Servants (PNS) at the Environmental Service Office of Jambi Province. The sampling technique used the census method, in which the entire population was included as respondents. Data were collected through questionnaires using a Likert scale and analyzed using the Partial Least Square (PLS) method with SmartPLS 3.0 software. The results show that competence has a positive and significant effect on motivation and employee performance. Training also has a positive and significant effect on motivation and employee performance. Furthermore, motivation is proven to act as an intervening variable that strengthens the influence of competence and training on performance. Thus, the higher the competence and the better the training provided, the greater the employee motivation, which ultimately leads to improved employee performance